Needs Analysis to Develop Learning Media Based on Scientific Literacy - Umul Fadlah; Indarini Dwi Pursitasari; Bibin Rubini (Jurnal Penelitian Pendidikan IPA, 2024)
Encouraging students to become more proficient in scientific literacy is crucial. Biology is the study of living things and the phenomena of life in their surroundings. A person who literates science is prepared to engage in meaningful discussions about science and technology, which require competence to explain phenomena scientifically, to evaluate and design scientific research, and to interpret data and evidence scientifically. This research uses quantitative approaches with correlational type. The samples in this research were about 105 junior high school students in Bogor, Indonesia. The purpose of this study to analyzing the needs in developing science literacy-based learning media. The result show that scientific literacy score is 51 categorized in medium category. The results suggest a need for science literacy-based educational media to enhance students' science literacy. Hence, the development of instructional media grounded in scientific literacy is essential to enhance students' ability to engage with and comprehend complex scientific concepts.